Association Between Family Support and Breastfeeding Success in a Neonatal Care Unit: A Study at Islam Hospital Surabaya Jemursari - Purwandira, Lina; Nurjanah, Siti; Hidaayah, Nur; Sari, Ratna Yunita (STIKep PPNI Jawa Barat, 2025)
Background: Successful breastfeeding is influenced by various factors, one of which is family support. Support from a husband, mother, or other close family members plays a crucial role in building a mother’s confidence and commitment to exclusive breastfeeding. Lack of emotional, informational, or instrumental support may lead to early weaning or the use of formula milk.Objective: This study aimed to analyze the relationship between family support and the success of breastfeeding in the neonatal room of Islam Hospital Surabaya Jemursari.Methods: A cross-sectional design was employed involving 48 postpartum mothers whose neonates were admitted to the neonatal room. Participants were selected using simple random sampling. The independent variable was family support, and the dependent variable was the success of breastfeeding. Data were collected using a validated structured questionnaire assessing the level of family support and breastfeeding outcomes. Statistical analysis was conducted using the Spearman rho correlation test with a significance level of α = 0.05.|Results: Among the 27 respondents who reported successful breastfeeding, the majority received sufficient family support, while a smaller proportion reported low support. Interestingly, among 21 respondents who also reported breastfeeding success, nearly half received less family support. The Spearman rho test yielded a p-value of 0.211, indicating no statistically significant relationship between family support and breastfeeding success (p > 0.05).Conclusion: This study found no significant relationship between family support and breastfeeding success in the neonatal unit. Further research with larger sample sizes and more detailed measurement tools is recommended to explore this relationship further.